2005
DOI: 10.1262/jrd.17027
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Localization of Antigen Presenting Cells and T Cells in the Utero-vaginal Junction after Repeated Artificial Insemination in Laying Hens

Abstract: Abstract. The goal of our present study was to observe whether the populations of antigen presenting cells (Ia+ cells) and T cell subsets (CD4+ and CD8+ T cells) change in the utero-vaginal junction (UVJ) of Rhode Island Red laying hens that showed dramatic declines in fertility after repeated artificial insemination (AI). Rhode Island Red laying hens were divided into two groups: a virgin group (R-V) and artificial inseminated group (R-AI), which was exposed to weekly AI for a period of 3 mo. Undiluted fresh … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…Using a low fertility line of hens subjected to repeated inseminations, Das et al (2005b) observed swollen SST lacking resident sperm and lymphocyte infiltration of the SST. In addition, these authors also noted that the mucosa surrounding the SST possessed increased numbers of antigen-presenting cells expressing MHC class II, CD4 + , and CD8 + T phenotypes (Das et al, 2005a). Concurrent with the increased numbers of these immunocompetent cells and the abnormal appearance of the SST was a decrease in the abundance of mRNA for estrogen receptor-α (Das et al, 2006b).…”
Section: Immunological Aspects Of Sperm Selection and Storagementioning
confidence: 90%
“…Using a low fertility line of hens subjected to repeated inseminations, Das et al (2005b) observed swollen SST lacking resident sperm and lymphocyte infiltration of the SST. In addition, these authors also noted that the mucosa surrounding the SST possessed increased numbers of antigen-presenting cells expressing MHC class II, CD4 + , and CD8 + T phenotypes (Das et al, 2005a). Concurrent with the increased numbers of these immunocompetent cells and the abnormal appearance of the SST was a decrease in the abundance of mRNA for estrogen receptor-α (Das et al, 2006b).…”
Section: Immunological Aspects Of Sperm Selection and Storagementioning
confidence: 90%
“…Thus, these reports suggest that TGFbs exert suppressive effect on T-and B-cell proliferation or differentiation. Previous report described that lymphocyte population was increased in UVJ and sperm were not stored in SST in infertile hens after AI (Das et al 2005b). Plasma cells were also shown in the UVJ of infertile hens (Van Krey et al 1987).…”
Section: Sperm Survivability and Tgfb In Hen Oviductmentioning
confidence: 91%
“…However, the precise mechanism of sperm survivability in the SST has not been established. There are reports that the leukocyte population was increased in UVJ after artificial insemination (AI) in infertile hens and the local immunity of vagina and UVJ may affect the sperm survivability (Higaki et al 1995, Zheng et al 2001, Das et al 2005b. Thus, one of the requirements for prolonged sperm survivability in hen oviduct may be to suppress the immune response to sperm stored in SST.…”
Section: Introductionmentioning
confidence: 99%
“…Here, the spermatozoa are stored and ultimately released for upward transport toward the infundibulum for ova fertilization [14]. In previous studies, the population of immune cells in the UVJ tissues of infertile hens significantly increased in hens receiving AI [15, 16], and infiltration of lymphocytes into the SSTs of hens with low fertility were observed [17]. Along these lines, Bakset reported that successful sperm storage in the SSTs depends on the immune privilege of the sperms which is thought to relate to an allergen residing in SSTs [18].…”
Section: Introductionmentioning
confidence: 99%